Perhitungan Energi Bagi Kebutuhan Pengepresan Kopra Pada Perancangan Mesin Press Minyak Kelapa - Alberto Hutauruk; Miduk Tampubolon; Lestina Siagian; Parulian Siagian; Richard A M Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2019)
An experiment has been conducted to determine the amount of deformation energy and energy per volume needed for the design of coconut oil press machines. By using a press tube with a diameter of 59 mm and by varying the load of press and speed of press the results obtained that to produce the optimal average volume of coconut oil are at the pressure load of 40 KN and the pressure rate of 6 mm / minute. The ideal energy per volume used to suppress coconut oil press machine is 6.106 J / m3.